2022
DOI: 10.1101/2022.08.15.503958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the hypothalamic oxytocin system and oxytocin receptor-expressing astrocytes in a mouse model of Prader-Willi syndrome

Abstract: Prader-Willi syndrome (PWS) is a neurodevelopmental disorder characterized by hyperphagia, obesity, developmental delay and intellectual disability. Studies suggest dysfunctional signaling of the neuropeptide oxytocin as one of the key mechanisms in PWS, and administration of oxytocin via intranasal or systemic routes yielded promising results in both humans and mouse models. However, a detailed assessment of the oxytocin system in mouse models of PWS such as the Magel2-deficient Magel2tm1.Stw mouse, is lackin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Albeit the presence of OTRs on glial cells has been described before, 26,27 their respective role was deemed insignificant or at least, not studied. However, this dogmatic view has recently been challenged and it became evident that physiologically and behaviorally‐relevant populations of OTR‐expressing astrocytes exist in various brain regions of mouse and rat 12,28–32 . In their original publication, Wahis and colleagues demonstrated the existence of strategically‐positioned and morphologically distinct population of OTR‐positive astrocytes in the central amygdala, which modulates comfort, anxiety and pain by orchestrating the activity of neurons within the central amygdala 31 .…”
Section: Glial Expression Of Functional Otrs and Their Role In Physio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit the presence of OTRs on glial cells has been described before, 26,27 their respective role was deemed insignificant or at least, not studied. However, this dogmatic view has recently been challenged and it became evident that physiologically and behaviorally‐relevant populations of OTR‐expressing astrocytes exist in various brain regions of mouse and rat 12,28–32 . In their original publication, Wahis and colleagues demonstrated the existence of strategically‐positioned and morphologically distinct population of OTR‐positive astrocytes in the central amygdala, which modulates comfort, anxiety and pain by orchestrating the activity of neurons within the central amygdala 31 .…”
Section: Glial Expression Of Functional Otrs and Their Role In Physio...mentioning
confidence: 99%
“…However, this dogmatic view has recently been challenged and it became evident that physiologically and behaviorally-relevant populations of OTR-expressing astrocytes exist in various brain regions of mouse and rat. 12,[28][29][30][31][32] In their original publication, Wahis and colleagues demonstrated the existence of strategically-positioned and morphologically distinct population of OTR-positive astrocytes in the central amygdala, which modulates comfort, anxiety and pain by orchestrating the activity of neurons within the central amygdala. 31 Intriguingly, they observed that OTRmediated activation of astrocytes preceded neuronal activation and inhibition of astrocytic OTRs almost entirely blocks the functionality of the local neuronal central amygdala microcircuit.…”
Section: Glial Expression Of Functional Otrs and Their Role In Physio...mentioning
confidence: 99%